A Fluorescent Reporter-Based Evaluation Assay for Antibacterial Components Against Xanthomonas citri subsp. citri - Long, Yunfei; Luo, Ruifang; Xu, Zhou; Cheng, Shuyuan; Li, Ling; Ma, Haijie; Bao, Minli; Li, Min; Ouyang, Zhigang; Wang, Nian; Duan, Shuo (Frontiers in Microbiology, 2022)
Xanthomonas citri subsp. citri (Xcc) is the agent of citrus bacterial canker (CBC) disease, which has significantly reduced citrus quantity and quality in many producing areas worldwide. Copper-based bactericides are the primary products for CBC control and management, but the problems derived from copper-resistant and environmental contamination have become issues of anxiety. Thus, there is a need to find alternative antibacterial products instead of relying on a single type of agent. This study developed a method to evaluate the inhibition of antibacterial agents using the fluorescence-labeled recombinant Xcc strain (Xcc-eYFP). The optimization of timelines and parameters for the evaluation of antibacterial agents involved the use of a Spark™ multimode microplate reader. This evaluation and screening method can be applied to bactericides, cocktail-mixture formulations, antagonistic bacteria, and derived metabolites. The results showed that the minimum inhibitory concentration (MIC) of commercial bactericides determined by fluorescence agrees with the MIC values determined by the conventional method. A screened cocktail-mixture bactericide presents more activity than the individual agents during the protective effects. Notably, this method has been further developed in the screening of Xcc-antagonistic bacterial strains. In summary, we provide a validated strategy for screening and evaluation of different antibacterial components for inhibition against Xcc for CBC control and management.